background image

Reloids are a special case of trans-reloids (take

A

=

B

).

In order to not repeat the entire theory of reloids for the more general case of trans-reloids, I

will describe properties of trans-reloids through reloids equivalent (in the sense I defined above for
filter objects) to them.

Definition 11.

I will call trans-reloids

f

and

g

composable

when Dst

f

=

Src

g

.

Definition 12.

Composition of trans-reloids is defined by the formula

g

f

=

\

R LD

(

Src

f

;

Dst

g

)

{

G

F

|

F

up

f , G

up

g

}

.

Composition of trans-reloids is a trans-reloid.

Theorem 13.

Let

f

,

g

,

f

,

g

are trans-reloids. Then

f

f

g

g

g

f

g

f

.

Proof.

There exist a binary relation

K

such that

K

up

f

,

K

up

f

, and

P

K

up

f

=

P

K

up

f

and a binary relation

L

such that

L

up

g

,

L

up

g

, and

P

L

up

g

=

P

L

up

g

.

g

f

=

T

R LD

(

Src

f

;

Dst

g

)

{

G

F

|

F

up

f , G

up

g

}

=

T

R LD

(

Src

f

;

Dst

g

)

{

G

F

|

F

P

K

up

f , G

P

K

up

g

}

=

T

R LD

(

Src

f

;

Dst

g

)

{

G

F

|

F

P

K

up

f

, G

P

K

up

g

} ∼

T

R LD

(

Src

f

;

Dst

g

)

{

G

F

|

F

P

K

up

f

, G

P

K

up

g

}

=

T

R LD

(

Src

f

;

Dst

g

)

{

G

F

|

F

up

f

,

G

up

g

}

=

g

f

.

Theorem 14.

The following are equivalent for every three composable trans-reloids

f

,

g

,

h

:

1.

h

=

g

f

.

2. There exist some set and reloids

f

and

g

on this set such that

f

f

,

g

g

, and

h

g

f

.

3. For every reloids

f

and

g

such that

f

f

,

g

g

we have

h

g

f

.

Proof.

(1)

(2).

Let

h

=

g

f

. Get

f

=

f

÷

(

A

B

C

)

2

and

g

=

g

÷

(

A

B

C

)

2

. Obviously

f

f

,

g

g

.

g

f

=

T

R LD

(

A

B

C

)

{

G

F

|

F

up

f

, G

up

g

}

=

T

R LD

(

A

B

C

)

{

G

F

|

F

up

f ,

G

up

g

} ∼

T

R LD

(

A

;

C

)

{

G

F

|

F

up

f , G

up

g

}

=

g

f

.

(2)

(3).

From the previous theorem.

(3)

(1).

Let

f

=

f

and

g

=

g

. We have

h

g

f

and thus

h

=

g

f

.

Theorem 15.

Composition of trans-reloids is associative.

Proof.

Let

f

:

A

B

,

g

:

B

C

,

h

:

C

D

are trans-reloids. Consider the reloids

f

=

f

÷

(

A

B

C

D

)

2

,

g

=

g

÷

(

A

B

C

D

)

2

,

h

=

h

÷

(

A

B

C

D

)

2

.

Then

g

f

g

f

and

h

g

h

g

thus

h

(

g

f

)

h

(

g

f

) = (

h

g

)

f

(

h

g

)

f

.

Thus

h

(

g

f

) = (

h

g

)

f

.

It is simple to show that trans-reloids with the given composition and identity functions as

identities form a category. I’ll call it

the category of trans-reloids

.

2.2.1 Some definitions for trans-reloids

Definition 16.

The

reverse

trans-reloid of a trans-reloid

f

is defined by the formula

up

f

1

=

F

1

|

F

up

f

1

 

.

Definition 17.

Domain

and

image

of a trans-reloid

f

are defined as follows:

dom

f

=

\

F

(

Dst

f

)

h

dom

i

up

f

;

im

f

=

\

F

(

Dst

f

)

h

im

i

up

f .

Preliminary definitions

3